Phenomenology, psychopathology and phenomenological psychopathology - Jerotić, Stefan; Pantovic-Stefanovic, Maja (Engrami, 2021)
The observation, description and definition of the structure of psychopathological phenomena make up the foundation of clinical psychiatry. Phenomenology can be defined as a group of philosophical principles that are dedicated to the systematic analysis of consciousness and its objects. Phenomenological psychopathology is the application of phenomenological principles to psychopathology. The goal of phenomenological psychopathology is to make explicit the subtle structures of pathological experience. Thus, the use of the phenomenological method enables us to disclose the indistinct or neglected psychopathological phenomena. It allows us to systematically construct a psychopathological taxonomy. This paper defines and summarizes the following topics: (1) phenomenology as a set of philosophical doctrines; (2) phenomenological psychopathology and its application in clinical work; (3) the significance of Karl Jaspers for phenomenological psychopathology and psychiatry; (4) contemporary trajectories of phenomenological psychopathology. A comprehensive understanding of the concept of phenomenological psychopathology is a prerequisite for the prices understanding of the subjective experience of a psychiatric patient.